Réponses

2012-10-23T18:36:02+02:00

f(x)=x³-30x²+112

1)lim(-infini)f(x)

f(x)=x³-30x²+112=x³(1-30/x+112/x³)

lim(-infini)1=1 et lim(-infini)-30/x=0 et lim(-infini)112/x³=0

d'où lim(-infini)(1-30/x+112/x³)=1+0+0=1 et lim(-infini)x³=-infini

donc lim(-infini)f(x)=(-infini)(1)=-infini

2)f(x)=(x-2)(ax²+bx+c)=ax³+bx²+cx-2ax²-2bx-2c=ax³+(b-2a)x²+(c-2b)x-2c

d'où ax³+(b-2a)x²+(c-2b)x-2c=x³-30x²+112

=> a=1, b-2a=-30, c-2b=0 et -2c=112 d'où a=1, c=-112/2=-56, b=-30+2a=-30+2=-28

=> f(x)=(x-2)(x²-28x-56)